2001
DOI: 10.1002/aic.690470918
|View full text |Cite
|
Sign up to set email alerts
|

Extended PLS approach for enhanced condition monitoring of industrial processes

Abstract: IntroductionThe detection and diagnosis of abnormal situations in the operation of industrial processes is a problem of considerable challenge that is attracting wide attention in both academe Ž . and industry. Nimmo 1995 showed that the U.S.-based petrochemical industry alone could save up to $10 billion per year if abnormal situations could be detected, diagnosed, and appropriately dealt with. The consequences of not being able to detect such abnormal situations range from increased operational costs to cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Studies on applications of PCA to process industries can be found in Akbaryan and Bishnoi (2001), Amand et al (2001), Kano et al (2001Kano et al ( , 2002, Kruger et al (2001), McAvoy (2002), Ü ndey and Cinar (2002), Wong and Wang (2003), Lee et al (2004), Miletic et al (2004).…”
Section: Principal Component Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Studies on applications of PCA to process industries can be found in Akbaryan and Bishnoi (2001), Amand et al (2001), Kano et al (2001Kano et al ( , 2002, Kruger et al (2001), McAvoy (2002), Ü ndey and Cinar (2002), Wong and Wang (2003), Lee et al (2004), Miletic et al (2004).…”
Section: Principal Component Analysismentioning
confidence: 98%
“…A popular application of PLS is to include process variables in the predictor matrix and product quality data in the dependent matrix, which can include off-line measurement data (Kruger et al, 2001). Such inferential models (also known as soft sensors) can be used for on-line prediction of product quality data.…”
Section: Partial Least Squarementioning
confidence: 99%
“…In particular, principal component analysis (PCA) and partial least squares (PLS) have been widely used for process monitoring and fault diagnosis [1][2][3][4][5][6]. Recently, independent component analysis (ICA) was employed for monitoring processes with non-Gaussian information, which can effectively extract high-order statistical information from process data [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…PLS is predominantly used for the modelling of intensity-based data that stem from infrared or Raman spectroscopy experiments, for example References [2,3]. The application of PLS to recorded data from the chemical industry is often concerned with statistical-based process monitoring of continuous [4] and batch processes [5].…”
Section: Introductionmentioning
confidence: 99%